Biofilm-Mediated Survival of Leptospira spp.: A Comprehensive Review on Molecular Basis and Control Strategies - Wijayanto, Robby; Zilfiarani, Chalida Nahendra; Fahlefi, Moch. Ilham Riza (Journal of Basic Medical Veterinary, 2025)
Leptospirosis is a significant tropical zoonosis, with a considerable burden on morbidity and mortality in humans as well as animals. One of the possible explanations is biofilm formation, which is the accumulation of EPS, eDNA, and c-di-GMP signals that respond to various environmental, antibiotic, or host-immune challenges. This review focuses on the molecular mechanisms underlying biofilm formation, ecological significance, connection to antimicrobial resistance, and the public health implications. Elucidation of the c-di-GMP regulatory networks, adhesin gene and protein expression, and other metabolic shifts account for the survival of Leptospira biofilms in autochthonous populations of aquatic habitats and kidney colonization of reservoir hosts. In addition, biofilms have been associated with long-term bacterial colonization, chronic urine stream associated with persistent bacterial shedding, and failed antibiotics. This scenario, from an epidemiological perspective, facilitates the emergence of anthropogenic infections, and perpetuates the endemic nature of the disease. From a disease-control perspective, biofilms increase the burden associated with persistent infections. This review emphasizes that, as a survival strategy, biofilms represent several potential avenues for the implementation of novel control strategies, including the use of antibiofilm agents, quorum-sensing inhibitors, and multi-epitope vaccines. The functional and integrated dissection of biofilms positioned Leptospira spp. to novel One Health-based control strategies for the disease.